1982 4th ASCOPE LABORATORIES TEST CORRELATION PROGRAMME ON C.F.R. ENGINE - Bustani Mustafa; E. Jasjfi (Scientific Contributions Oil and Gas, 1985)
Member countries taking part in this correlation programme are Indonesia as coordinator with seven laboratories participating.